Properties of Ply and Cord Yarns from Sacred Lotus Fibers (Nelumbo nucifera Gaertn.) Classified as Z on Z Twist - Panbua, Nathasar (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
The objectives of this research were to study the physical properties of lotus ply yarns and cord yarns classified as Z on Z twist. The comparison of types of lotus stalk, the amounts of yarn affecting the yarn number, tenacity and elongation were studied. The experimental design used was factorial experiment in CRD. The preparation process of lotus fiber was done by stretching method from the milky latex inside the stalk of lotus using flower stalks and leaf stalks. The ply yarns spun in 2 and 3ply and the cord yarns spun in 2-2, 2-3, 3-2, and 3-3ply. The yarns were tested for physical properties according to ASTM. The results were as follows: the ply yarns had values of tenacity obtained ranged from 5.446-6.090 g/tex. The 2ply yarn of flower stalks had the highest tenacity. The yarn number obtained was 224.878-270.550 tex. The values of elongation obtained ranged from 3.351-4.182%. The 3ply yarn of leaf stalks had the highest the yarn number and elongation. The cord yarns had the yarn number obtained at 456.514-972.144 tex. The values of tenacity obtained ranged from 2.227-3.994 g/tex. The 3-3ply yarn of leaf stalks had the highest yarn number and tenacity. The values of elongation obtained were between 8.098-9.266%. The 2-3ply yarn of flower stalks had the highest elongation. Ply yarns revealed that the type of the lotus stalk significantly affected the yarn number at 0.05 level. The amount of yarn significantly affected yarn number and elongation at 0.01 level. Cord yarns showed that the type of the lotus stalk significantly affected yarn number at 0.01 level. The amount of yarn significantly affected yarn number, tenacity and elongation at 0.01 level.